Perceptions and Practices Related to Twice-Exceptional Learners in K-12 American Private Schools in Dubai - FAKIH, MIRNA KHALIL (2024)
Recent studies have shown a gap in the literature about twice-exceptional learners, which has led to a lack of awareness and different perceptions among stakeholders due to the comorbidity they possess. The UAE is indomitable towards earning the first class in education, which is incarnated in its ‘Golden Jubilee" and the new vision of 2030, especially educating learners with SEND. Therefore, holistic efforts exerted by KHDA have been witnessed in 2017 by amending the inclusive education policy across the UAE nation, along with “the National Policy for Empowering People of Determination." However, the Ministry of Education and Dubai Inclusive Education policy framework have not recognized "twice-exceptional learners" as an individual category who, from equity and social justice, deserve all rights to be fairly educated, yet they have been marginalized in inclusive settings, hence the significance of this study. This study aimed to investigate perceptions, practices, and awareness about twice-exceptional learners in K–12 American private schools in Dubai, with a great focus on the kindergarten phase as a starting point in which issues related to identification, support, and provision constitute a great challenge. Additionally, the contribution of twice-exceptional learners’ parents and their reflections about their challenges and experiences with their twice-exceptional children have been an important factor that has added great value to this study. A concurrent parallel mixed method design was employed in the study; quantitative data was collected using a questionnaire to survey K–12 teachers; qualitative data was collected using semi-structured interviews with stakeholders; observations of twice-exceptional learners in mainstream classrooms,and document analysis of policies, guidelines, frameworks, and schools’ documents. Quantitative data have been analyzed using SPSS, and qualitative data have been analyzed using thematic analysis. Results of the study have revealed that stakeholders and K–12 teachers have shown different perceptions, experiences, and low levels of awareness towards the education of twice-exceptional learners due to many factors and challenges. The recommendations from this study emphasize future improvement through establishing a comprehensive K–12 policy framework specially designed to shape the education of 2e learners, provide continuous professional development for K–12 teachers, and increase the quality of provision in mainstream settings. This study will provide future suggestions for governmental entities and private schools to reform their inclusion policies and guidelines to meet the individual needs of 2E learners, in addition to its contribution to the literature for its uniqueness through changing the perceptions of stakeholders and enhancing their awareness about twice-exceptional learners in American private schools in Dubai, in higher education, in other Emirates, and other countries.